Northern archaeology and cosmology a relational view - Herva, Vesa-Pekka (Routledge, 2020)
"In its analysis of the archaeologies and histories of the northern fringe of Europe, this book provides a focus on animistic-shamanistic cosmologies and the associated human-environment relations from the Neolithic to modern times. The North has fascinated Europeans throughout history, as an enchanted world of natural and supernatural marvels: a land of light and dark, of northern lights and the midnight sun, of witches and magic, and of riches ranging from amber to oil. Northern lands conflate fantasies and realities. Rich archaeological, historical, ethnographic and folkloric materials combine in this book with cutting-edge theoretical perspectives drawn from relational ontologies and epistemologies, producing a fresh approach on the prehistory and history of a region that is pivotal to understanding Europe-wide processes, such as Neolithization and modernization. This book examines the mythical and actual northern worlds, with northern relational modes of perceiving and engaging with the world on the one hand and the 'place' of the North in European culture on the other. This book is an indispensable read for scholars of anthropology and folklore in northern Europe, as well as those with an interest in the political and geographical conflicts that can occur in this region. It provides a deep-time understanding of globally topical issues and conflicting interests, as expressed by debates and controversies around Arctic resources, nature preservation, and indigenous rights"--